Gender Analysis in terms of Attitudes and Self-Efficacy of Science Subjects for Junior High School Students - M. Dwi Wiwik Ernawati; Asrial Asrial; Dwi Agus Kurniawan; Ahmad Mansur Nawahdani; Rahmat Perdana; Rahmi Rahmi (Jurnal Penelitian Pendidikan IPA, 2021)
The purpose of this study was to determine the comparison of students' attitudes and self-efficacy based on gender, and to determine the relationship between students' attitudes and self-efficacy towards science subjects. This research uses quantitative research with survey method. The sample in this study was 74 students from SMPN 1 Muaro Jambi in Muaro Jambi district. The sampling technique used is purposive sampling. There are two instruments in this study, namely attitudes towards science and self-efficacy. The results of the T-test of student attitudes towards science subjects obtained were sig. (2-tailed) < 0.05, so there were differences in student attitudes towards science subjects, both female and male students in class VIII A and class VIII B. The results of the T-test of students' self-efficacy on science subjects obtained a value of sig.(2-tailed) < 0.05, so there are differences in student self-efficacy on science subjects, both female students and male students in class VIII A and class VIII B. While the results of the correlation test between attitudes and students' self-efficacy towards science subjects class VIII A and VIII B showed a value of sig. (2-tailed) < 0.05, then there was a relationship between students' attitudes and self-efficacy towards subjects’ science lessons, both female students and male students in class VIII A and class VIII B.